Multibrella / Ahmad Ammar Aidil Ahmad Nizar ... [et al.]. - Ahmad Nizar, Ahmad Ammar Aidil; Khairul Azwa, Khairul Haziq Zikry; Kamaruddin, Muhammad Amar; Norhisham, Muhammad Ikmal Hakimi; Zamzuree, Muhd Ameer Danish (2025)
Wet Center is an innovative umbrella that prioritizes user convenience and ease of use while addressing harsh weather conditions. This inventive invention has innovative components that address a range of environmental issues, surpassing the capabilities of conventional umbrellas. Wet Center's integrated heater guarantees that users will remain warm and comfy in cold or hot conditions. It is appropriate for all seasons and has a small fan to assist ventilation and increase its usefulness in hotter regions. These well-considered elements show how committed we are to provide a solution that smoothly adjusts to shifting weather conditions. Wet Center's also has solid construction and weather-resistant materials ensure durability, meeting the demands of modern consumers who value both practicality and long-lasting quality. In addition to its heating and cooling capabilities. Wet Center offers visor protection to shield users from harmful UV rays during sunny days. This added feature ensures safety and comfort, making the product ideal for use in a variety of settings, whether on a rainy commute, a sunny outing, or an unexpected storm. Additionally, Wet Center's expandable design makes it ideal for families, groups of friends, or coworkers who need dependable protection together.